Is part-time sick leave helping the unemployed? - Daniela Andrén (Örebro University School of Business, 2011)
Using a discrete choice one-factor model, we estimate mean treatment parameters and distributional treatment parameters to analyze the effects of degree of sick leave on the probability of full recovery of lost work capacity for employed and unemployed individuals, respectively. Our results indicate that one year after the sick leave spell started, the average potential impact of part-time sick listing on an individual randomly chosen from the population on sick leave was positive for both groups, but the average effect on those who actually were on part-time sick leave was positive only for the employed, and negative for the unemployed.
Keywords: I12; J21; J28; 330; unemployed; part-time sick leave; selection; unobserved heterogeneity; treatment effects